PECULIARITIES OF REASONING IN PRIMARY SCHOOL PUPILS - Madirimova Momajon Raximboyevna (International Scientific and Current Research Conferences, 2025)
One of the main goals of modern education is to help primary school students learn how to think logically. This is important because it helps them understand, solve problems, and learn by thinking about what they have learned in all subjects. At this stage, children evolve from intuitive, syncretic thinking to more organized reasoning, shaped by education, language acquisition, and social engagement. This article examines the psychological and pedagogical characteristics of reasoning during the early school years, drawing upon J. Piaget's concepts regarding the transition from preoperational to concrete-operational thought and Vygotskyan perspectives on the social dimensions of higher mental functions. It emphasizes the preeminence of tangible representations, the incremental development of logical operations, and the reliance of children's arguments on context, adult supervision, and linguistic resources. Recent research on argumentation and dialogic teaching in primary classrooms is synthesized to demonstrate how teacher inquiries, collaborative problem-solving, and feedback influence the quality of students' reasoning. The article concludes with practical implications for instructional design aimed at deliberately fostering explanatory, justificatory, and reflective reasoning from the initial years of education.